Acute toxicity of the aqueous-methanolic Moringa oleifera (Lam) leaf extract on female Wistar albino rats - Okumu, Mitchel O.; Mbaria, James M.; Kanja, Laetitia W.; Gakuya, Daniel W.; Kiama, Stephen G.; Ochola, Francis O.; Okumu, Paul O. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Herbal preparations are widely assumed to be safe on oral administration and therefore the documentation of the toxic potential of some herbal concoctions used as medicine and nutrients is limited. Moringa oleifera (MO) is a plant that is gaining tremendous popularity in rural communities in Kenya as a means of offsetting nutritional and medicinal needs. However, very little is known about the safety of the plant on oral administration. Thus, the aim of the current study was to assess the biochemical and histological changes in the liver following the administration of an aqueous-methanolic (AQ-ME) MO leaf extract in female Wistar albino rats. Methods: Acute oral toxicity study on the AQ-ME MO leaf extract was conducted by the use of the limit test dose of the up and down procedure (OECD guideline number 425) with slight modifications. Briefly, ten (10) healthy, nulliparous, non-pregnant female Wistar strain albino rats aged 8-12 weeks and weighing 180±20 grams were used for the study. These animals were randomly selected into two groups; control and treatment group each having five (5) animals. They were then labelled to enable identification and control group animals were orally administered with physiological buffer saline once daily over a 48-hour period. The five (5) rats in the treatment group were dosed orally one at a time and once daily with a 2000 mg/kg dose of the AQ-ME MO leaf extract to determine the median lethal dose over a 48 hour period. Blood was then collected and used to prepare serum for biochemical analysis of aspartate amino transferase (AST), alanine amino transferase (ALT) and total bilirubin (TB) which are important biomarkers of liver dysfunction. Biochemical assays of these enzymes were performed using the method of the International Federation of Clinical Chemists (IFCC). Death was used as an endpoint, livers harvested and used to prepare transverse sections for histopathological examination. These sections were stained using the haematoxylin and eosin (H&E) method and observed for pathological changes using an optical microscope. Results: A 2000 mg/kg oral dose of AQ-ME MO leaf extract caused a significant (p<0.05) increase in the mean levels of AST but a non-significant (p>0.05) increase in the mean levels of total bilirubin in the treatment group relative to the control group. On the other hand, the extract caused a non-significant (p>0.05) decrease in the mean levels of ALT in the treatment group relative to the control. The post mortem analysis of the hepatic index (liver to body weight ratio) revealed that there was a non-significant increase (p>0.05) in the hepatic index of the treatment group relative to the control. However, the transverse liver sections of treatment group animals showed mild distortions in the architecture of liver cells. Conclusions: Based on these results, the LD50 of the AQ-ME MO leaf extract was found to be >2000 mg/kg in female wistar albino rats.